IMPLIKASI KEBIJAKAN “PENDAERAHAN” PENGELOLAAN PBB SETELAH BERLAKUNYA UU NO. 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Pamuji, Kadar (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Local tax policies according to local tax laws and new levies which gives breadth to the local taxation authority is done by expanding the tax base. Giving to the local taxation authority have been duly carried out to confirm the alignments to the process of democratization. The problem is